Keamanan Data User Pada Jaringan Wirelles Menggunakan Two Factor, Password Dan Mac Address Filtering Di Jurusan Teknik Komputer - slamet widodo; Adi Sutrisman; M. Miftakul Amin; Muhammad fernaldo harefa; Muhammad Aulia Farhan; Muhammad Reinaldo (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Users of internet network facilities are needed to find references as well as add insight. One of the internet networks used is a wireless network in the form of hotspot technology. Hotspot networks are an important requirement in activities implemented in universities. Frequent attacks that disrupt the internet network such as Wireless Hacking. This study discusses user data security applications and wireless security systems using two factors, passwords and MAC address filters in the computer engineering department. Therefore, to overcome this problem, network security was built with firewall settings, namely filter rules and NAT. Based on these problems, the discussion that will be reviewed is about making user data security applications that are useful for accommodating the user's MAC address and making hotspots on Mikrotik, and testing the designed hotspot network. Based on the test results, it can be concluded that the firewall can overcome illegal hotspot users in the MikroTik hotspot. With the development of user data security applications and internet security using a firewall, setting the filter rules and NAT helps users to minimize the occurrence of illegal users. Firewalls are able to filter access to a computer using a list of permissions (permissions list) that is made based on the MAC address. By registering the MAC-Address, illegal users who are not registered in the network cannot easily access wireless networks in the Computer Engineering department. Keywords: Firewall, Hotspot, Mac-Address-Filter, Mikrotik.